GEJALA KLINIS SEBAGAI PREDIKTOR PADA KARSINOMA SEL BASAL - Ratih Pramuningtyas; Prasetyadi Mawardi (Universitas Muhamadiyah Surakarta, 2012)
Basal Cell Carcinoma (BCC) incidence is 75% of all skin cancers. BCC rarely causing mortality, but morbidity is high. Clinical diagnostic is the early detection of BCC suspicion, therefore, we required specific criteria that help to establish the clinical diagnosis. The objective of this study was to know the clinical sign as a predictor of basal cell carcinoma. Ten patients with skin tumors who came to dermatovenereological department of Dr. Moewardi hospital were included in this study. Clinical diagnosis using clinical criteria from keratinocyte carcinoma in A Cancer Journal For Clinicians in 2011 (Teleangiectasion, raise border, erythematous with bleeding, pigmentation, translucent appearance, and scarlike appearance) was used as reference of clinical diagnostic criteria. Histopathological examination was performed as a gold standard. All 10 subjects had histopathological finding consistent to BCC. The clinical examination like pigmentation were found in all subjects while teleangiectasia, raise border, erythema with bleeding were found on 9 subject. Translucent appearance was found on 6 subjects. While scarlike appearance was absent in all subjects. The criteria from keratinocyte carcinoma in A Cancer Journal For Clinicians in 2011 can be used to diagnosed BCC clinicallyKeywords : Basal cell carcinoma, Clinical Diagnostic Criteria